2022
DOI: 10.1038/s41598-021-04403-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Te- and Fe-doping on the superconducting properties in FeySe1−xTex thin films

Abstract: High quality FeySe1−xTex epitaxial thin films have been fabricated on TiO2-buffered SrTiO3 substrates by pulsed laser deposition technology. There is a significant composition deviation between the nominal target and the thin film. Te doping can affect the Se/Te ratio and Fe content in chemical composition. The superconducting transition temperature Tc is closely related to the chemical composition. Fe vacancies are beneficial for the FeySe1−xTex films to exhibit the higher Tc. A 3D phase diagram is given that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
1
11
1
Order By: Relevance
“…All the films have a thickness of 330 nm. The presence of volatile Se and Te elements can cause the composition of the FeSeTe thin films to be inconsistent with that of the targets [24], and such compositional inconsistency varies with the substrate temperature due to the re-evaporation of film components from the substrate [25][26][27]. Therefore, in this work, the deposition temperature was tuned in the range of 350 • C-500 • C to obtain a series of Fe y Se x Te 1−x thin films with different compositions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the films have a thickness of 330 nm. The presence of volatile Se and Te elements can cause the composition of the FeSeTe thin films to be inconsistent with that of the targets [24], and such compositional inconsistency varies with the substrate temperature due to the re-evaporation of film components from the substrate [25][26][27]. Therefore, in this work, the deposition temperature was tuned in the range of 350 • C-500 • C to obtain a series of Fe y Se x Te 1−x thin films with different compositions.…”
Section: Methodsmentioning
confidence: 99%
“…Although crystalline lattice behaving instable for bulk materials, tetragonal phase can be stabilized utilizing the compressive stress from the substrate for FeSeTe films with Fe deficiency. It has been reported that FeSeTe superconductor still exhibits high T c at Fe content of 0.8 or less [11,14,24]. However, systematic study of the Fe dependence on superconductivity is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that a deviation in the chemical composition between the nominal target and the final films was consistently observed in FST thin films produced by PLD . This phenomenon is likely due to differences in the transfer and growth rates of Fe, Se, and Te elements during the deposition process …”
Section: Resultsmentioning
confidence: 92%
“…48 This phenomenon is likely due to differences in the transfer and growth rates of Fe, Se, and Te elements during the deposition process. 49 TEM was utilized to investigate the microstructure and superconducting properties of the FST thin films, with a particular focus on 200 nm-(Figure 3a,b) and 1 μm-thick films (Figure 3c,d). In Figure 3a, the LMO buffer layer showed different white and black columnar contrast, indicating different types of grains.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[6] Variations in the composition, including stoichiometry and mixed phases, have also been implemented to modify the electronic structure of materials or obtain synergic effects of different phases. [7][8][9][10][11][12] The microstructure and composition of thin films can be engineered by adjusting the film deposition conditions or performing postdeposition treatments that consider the intrinsic properties of the material.…”
Section: Introductionmentioning
confidence: 99%